Isolation and Characterization of Plant-Derived Exosome-Like Nanoparticles (PDEN) from Sapodilla Fruit (Manilkara zapota) as an Antioxidant Agent in 1BR3 Cell Line - Noeng, Anastasia; Barlian, Anggraini (HAYATI Journal of Biosciences, 2025)
Plant-derived exosome-like nanoparticles (PDENs) have emerged as promising natural nanocarriers with potential applications in biomedicine and cosmetics due to their biocompatibility, stability, and intrinsic bioactivity. The objective of this research is to isolate, characterize, and analyze the effects of MZ-PDENs on 1BR3 cells. MZ-PDENs were isolated using filtration, differential centrifugation, and polymer-based precipitation. MZ-PDENs were characterized for their physiochemical properties, size, shape, and antioxidant activity. In vitro, bioactivities were conducted by measured cytotoxicity, proliferation assays, UVB protection, and migration assays. Results showed that MZ-PDENs possess strong antioxidant properties, are efficiently internalized by cells, and promote skin cell regeneration after UVB-induced damage. These findings suggest that MZ-PDENs have the potential as antioxidant agents for cosmeceutical applications and warrant further investigation in vivo models.